Cementation of Bioproducts Generated from Biodegradation of Radioactive Cellulosic-Based Waste Simulates by Mushroom. (29th November 2012) - Eskander, S. B.; Abd El-Aziz, S. M.; El-Sayaad, H.; Saleh, H. M.
Abstract : The current work was devoted to study the solidification of bioproducts originated from the bioremediation of mixture of solid cellulose-based radioactive waste simulates using a mushroom ( Pleurotus pulmonarius ), in Portland cement. The obtained solidified waste form was subjected to mechanical integrity qualification after curing periods of 28 and 90 days. Chemical performance of the cement-waste form was also evaluated in different leachant media during 540 days. The results obtained gave useful information about the mechanical, physical, and chemical performances of the final cement-waste form incorporated the radioactive bioproducts. Moreover, it indicated that cement can provide a highly durable form that ensures a long-term stability of the solidified waste material and can act as a first barrier against the release of radiocontaminants from radioactive wastes to the surrounding environment.